Das ländliche Japan zwischen Idylle und Verfall Diskurse um Regionalität, Natur und Nation - Lewerich, Ludgera / Sieland (Kultur- und Sozialwissenschaftliche Japanforschung, 2020)
Against the background of demographic change, recession, the Tōhoku triple disaster in 2011, and the discourse on environmental protection, Japan's regions have once again become the focus of attention. This volume deals with current developments and problems in the revitalization of Japan's rural regions and discusses representations and (re-)constructions of nature, land, and ruralism.